2016
DOI: 10.1111/tbed.12561
|View full text |Cite
|
Sign up to set email alerts
|

Differential Cell Composition and Cytokine Expression Within Lymph Node Granulomas from BCG-Vaccinated and Non-vaccinated Cattle Experimentally Infected with Mycobacterium bovis

Abstract: Cattle vaccination against bovine tuberculosis (bTB) has been proposed as a supplementary method to help control the incidences of this disease. Bacillus Calmette-Guérin (BCG) is currently the only viable candidate vaccine for immunization of cattle against bTB, caused by Mycobacterium bovis (M. bovis). In an attempt to characterize the differences in the immune response following M. bovis infection between BCG-vaccinated and non-vaccinated animals, a combination of gross pathology, histopathology and immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
42
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 42 publications
11
42
3
Order By: Relevance
“…This may be due to the fact that the lesional pattern is too acute for the intervention of this cell population. This finding has been described in other diseases caused by intracellular pathogens such as Mycobacterium bovis (Salguero et al 2016). However, the role of these 'nests' in the host immune response is not well understood.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…This may be due to the fact that the lesional pattern is too acute for the intervention of this cell population. This finding has been described in other diseases caused by intracellular pathogens such as Mycobacterium bovis (Salguero et al 2016). However, the role of these 'nests' in the host immune response is not well understood.…”
Section: Discussionsupporting
confidence: 54%
“…This finding has been described in other diseases caused by intracellular pathogens such as Mycobacterium bovis (Salguero et al . ). However, the role of these ‘nests’ in the host immune response is not well understood.…”
Section: Discussionmentioning
confidence: 97%
“…tracheobronchial or mediastinal) [26], other studies have not identified which thoracic lymph nodes were examined or have pooled findings from both tracheobronchial and mediastinal lymph nodes [14, 16, 19, 21]. Disparate cytokine expression patterns between tracheobronchial and caudal mediastinal lymph nodes, as seen in the present study may be partially due to the afferent lymphatics serving these closely associated lymph nodes.…”
Section: Discussionmentioning
confidence: 62%
“…One study found greater TGF-β by IHC in late stage bovine granulomas compared to early stage granulomas [10]. Two separate studies found lower expression of TGF-β mRNA in stage IV granulomas of cattle compared to stage I granulomas [19] with increased expression in stage II granulomas [14]. In macaques, TGF-β may be a chief cytokine in driving tissue repair in active tuberculosis [34].…”
Section: Discussionmentioning
confidence: 99%
“…infection. These have also been used in other granulomatous diseases that share some, though not all properties with VL [ 15 18 ]. Additionally these techniques can be utilised to evaluate the cellular mechanism of new vaccines, drugs and treatment regimens [ 19 21 ].…”
Section: Discussionmentioning
confidence: 99%